Reactive oxygen species level defines two functionally distinctive stages of inflammatory dendritic cell development from mouse bone marrow - Sheng, K.; Pietersz, G.; Tang, C.; Ramsland, Paul; Apostolopoulos, V. (American Association of Immunologists, 2010)
Reactive oxygen species (ROS) have been implicated in various physiological activities. However, their role in dendritic cell (DC) activation and generation has not been investigated. Using the bone marrow-derived GM-CSF-induced ex vivo DC model, we characterize how induction of ROS correlates with inflammatory DC functionality and expansion. We describe that the functionality of GM-CSF-induced DCs is distinct in two developmental stages. Whereas division of DC-committed hematopoietic progenitor cells (HPCs) neared completion by day 6, the level of ROS soared after day 4. Day 3 ROSlo DCs were highly responsive to TLR stimuli such as LPS and zymosan by rapid upregulation of CD80, CD86, and MHC class II, in contrast to the low response of day 6 ROShi DCs. ROShi DCs could not initiate and sustain a significant level of NF-?B phosphorylation in response to LPS and zymosan, although demonstrating hyperactivation of p38 MAPK by LPS, in a fashion disparate to ROSlo DCs. ROSlo DCs stimulated a higher level of allogeneic and OVA-specific T cell proliferative responses, although ROShi DCs were much more proficient in processing OVA. In response to pathogenic stimuli, ROShi DCs also demonstrated rapid cellular adhesion and H2O2 release, indicating their role in immediate microbial targeting. Moreover, HPC expansion and DC generation were dependent on the surge of ROS in an NADPH oxidase-independent manner. These findings point to the potential role of cellular ROS in mediating functionality and development of DCs from HPCs during inflammation. Copyright © 2010 by The American Association of Immunologists, Inc.